Correlation of fine needle aspiration cytology with histopathology in the diagnosis of thyroid swellings - Babu, Sarath Babu Kumara; Raju, Rathan; Radhakrishnan, Shankar (International Surgery Journal, 2016)
Background:Fine needle aspiration cytology (FNAC) is now being accepted as the most cost-effective, minimal invasive technique with very low incidence of complications in the diagnosis of most of the thyroid lesions with an added advantage of segregating the patients of solitary thyroid nodule (STN) into operative and non-operative groups. Hence the aim of the present study is to determine the accuracy of FNAC in terms of sensitivity, specificity, positive predictive value and negative predictive value in comparison with histopathology in the diagnosis of a thyroid swelling Methods: A prospective longitudinal study was undertaken over a period of 1 year from Jan 2015 to Dec 2015 at the out-patient department of Annapoorana medical college and hospital. Patients with visible thyroid swelling with a solitary nodule, in euthyroid state and with no other serious medical disorders were included in our study. FNAC was performed with 23gauge needle, smears were fixed with ether-95% alcohol solution, and staining was performed using papanicolau’s staining. The thyroid specimen which was excised during the thyroidectomy procedure was processed in automated tissue processing units and sent for histopathological examination. Results:The validity of FNAC in terms of sensitivity and specificity was assessed by comparing it with the histopathological examination. The sensitivity of FNAC in detecting all the benign and malignant type of thyroid lesions was found to be in the range of 80–100%, whereas the specificity and the positive predictive value was almost 100% and the negative predictive value was between 98-100%, for all the lesions detected by FNAC. So this shows the accuracy of detection of lesions through FNAC is almost 94%. Conclusions:The use of FNAC has reduced the number of patients with solitary thyroid nodules undergoing unnecessary surgery and has led to proper planning of surgery in malignant cases.